NOVEL STARCH SOLUTION PREPARED FROM THE STARCH IN NAOH/THIOUREA/UREA AQUEOUS SOLUTION AND ITS APPLICATION AS SURFACE SIZING AGENT - Xu-Qing Wang; Xiao-Fan Zhou (BioResources, 2011)
Novel starch solutions were prepared by dissolving starch in NaOH/ thiourea/ urea aqueous solution, and they were further used as a surface sizing agent at high solids content in papermaking to improve the surface strength of papers. Two methods were adopted to dissolve the starch. In method A dry starch granules were directly added into the prepared solution. In method B a starch slurry was mixed with the prepared solution. The results revealed that method B was more effective than method A to achieve a lower viscosity of the starch solution. Dissolving temperature played an important role in dissolution of the starch. The viscosity values decreased with a decrease in the temperature of sample preparation. The starch dissolved in 4 wt% NaOH – 3 wt% urea – 3 wt% thiourea aqueous solution at -10°C were optimized to do the further application experiments. This kind of starch solution had lower viscosity and reached better viscosity-temperature stability, the viscosity was stable over a broad range of temperatures, and it also can be stored for over one month under room temperature. The surface sized papers with them had outstanding surface strength. Moreover, the prepared starch solutions were investigated by infrared spectroscopic analysis and scanning electron microscope, respectively, showing the structure of the starch solution.